Ruins to riches the economic resurgence of Germany and Japan after 1945 - Stokes, Raymond G. 1956- (Cambridge University Press, 2024)
"Between 1945 and 1960, Germany and Japan rocketed from crushing defeat to become two of the five largest economies in the world - positions they have maintained since. What accounts for this remarkable transformation? In this uniquely comparative account, Ray Stokes examines the spectacular resurgence of Deutschland AG and Japan Incorporated"
Keywords: Geschichte 1945-2023; Wirtschaftsentwicklung; Japan; Deutschland; Germany / Economic conditions / 1945-1990; Germany / Economic conditions / 1991-; Japan / Economic conditions / 1945-